2020
DOI: 10.1101/2020.03.10.986315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogel mechanical properties are more important than osteoinductive growth factors for bone formation with MSC spheroids

Abstract: Mesenchymal stromal cells (MSCs) can promote tissue repair in regenerative medicine, and their therapeutic potential is further enhanced via spheroid formation. We demonstrated that intraspheroidal presentation of Bone Morphogenetic Protein-2 (BMP-2) on hydroxyapatite (HA) nanoparticles resulted in more spatially uniform MSC osteodifferentiation, providing a method to internally influence spheroid phenotype. Stress relaxation of hydrogels has emerged as a potent stimulus to enhance monodispersed MSC spreading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To this end, many studies have found that culturing cells in a 3D spheroid environment enhances their therapeutic potential and survival. 3 These 3D spheroids are self-assembled aggregates of cells and more closely resemble the tissue microenvironment. To date, several different stem cell lineages have been formed into spheroids including hiPSCs and mesenchymal stem cells (MSCs) derived from umbilical cord tissue, endothelial cells, hepatocytes, adipose, smooth muscle, bone marrow, and menstrual blood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, many studies have found that culturing cells in a 3D spheroid environment enhances their therapeutic potential and survival. 3 These 3D spheroids are self-assembled aggregates of cells and more closely resemble the tissue microenvironment. To date, several different stem cell lineages have been formed into spheroids including hiPSCs and mesenchymal stem cells (MSCs) derived from umbilical cord tissue, endothelial cells, hepatocytes, adipose, smooth muscle, bone marrow, and menstrual blood.…”
Section: Introductionmentioning
confidence: 99%
“…13,16,17 In comparison to the traditional culture technique of cells in a monolayer, cells cultured as spheroids have demonstrated enhanced cell-survival, paracrine factor secretion, and tissue forming potential. 3,4,6,8,9,[18][19][20][21] They also have higher levels of tissue-specific gene expression and increased exosome production. 10,22 Overall, spheroids enhance biological processes relating to immunity, inflammation, angiogenesis, and wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the biomechanical properties of cells are significantly regulated by the interplay between them and the extracellular matrix (ECM) [20,21]. The ECM regulates cellular behaviors via stimulus-responsive systems [22,23]; the cells identify the effective stimulus from the surrounding physical and chemical environment via transmembrane specific receptors, and the signal is transduced, resulting in the alteration of cellular phenotypes [24]. Of note, the collective performance of cells in 3D multicellular culture systems is attributed not only to the behavior of single cells but also to cell-cell and cell-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%